The Positive Report Of benson Relaxation For Acute Miocard Infark Pain: A Case Report Study - Dwi Nur Rahmantika Puji Safitri; Sri Rejeki; Edy Soesanto; Muhammad Ali (South East Asia Nursing Research, 2021)
Structured Acute Myocardial Infarction (AMI) is myocardial necrosis caused by inadequate blood supply due to acute blockage of the coronary arteries. Typical signs and symptoms experienced in AMI patients are chest pain such as squeezing, pressing, stabbing, heat or being crushed by heavy objects. Giving pharmacological therapy such as oxygen, nitroglycerin and aspirin can reduce AMI pain, but if the effects of the drug begin to decrease the pain will back, so complementary therapy is needed to help reduce pain in AMI patients. The purpose of the research is to evaluate Benson's relaxation effect in reducing chest pain in acute myocardial infarction (AMI). The descriptive method was used by involving 2 subjects who experience chest pain. The intervention was carried out once a day for 2 days with an intervention duration of 30 minutes. The results of the evaluation were obtained, there was a decrease in both patients from 5 scales to 2 scales in patient 1 and 1 scale in patient 2. The combination of both pharmacological therapy and Benson relaxation can reduce the scale of pain. Benson relaxation can be used as a complementary therapy in reducing pain in AMI patients.